Management of Root Rot Caused by Curvularia spp. on Ludwigia repens using Biocontrol Agents - Y. Tharmili, G. Mikunthan; V. Jegathambigai, A. Sivinningen (Proceeding of the 3 rd international conference on Dry Zone Agriculture, 2017)
Ludwigia repens is the most popular ornamental aquarium plant cultivated in Green Farms (Pvt) Ltd., Marawila in Sri Lanka for export purpose. Recently, a root rot disease was detected to be a major problem in the cultivation of L. repens. This study was aimed to diagnose the problem and to identify the causal agent of the root. The findings of this study will assist the growers to mitigate the problem and to avoid losses due to returning of shipments from Europe. The fungus observed in roots of L. repens was isolated. After one day of incubation at 30 °C, immature mycelium was cottony white in color and irregular in shape. After 7 days of incubation at 30 °C, mature colonies were white to black in color. Microscopic observations revealed the presence of light brown to dark brown conidiophores present as single or as groups. The septate and single conidiophores were straight or slightly curved. Conidiophores were 2-4 celled. The median septum was observed as a black band and the cells at each end of the conidia were pale. The intermediate cells were brown or dark brown. Mature mycelium was observed as septate. Based on the morphological characteristics, the fungus was identified as Curvularia spp. The infection of Curvularia spp. on L. repens was confirmed through Koch’s postulates. Trichoderma viride (75%) and T. asperellum (65%) and T. harzianum (84%) showed high percentage of inhibition against Curvularia in dual culture. Compared to other botanicals, sulphur and Ocimum tenuiflorum was the best to control the rot disease (100%). Compared to other treatments, this could be achieved by O. tenuiflorum due to its antifungal properties. The chemical compound present in O. tenuilorum completely inhibited the growth of the Curvularia spp. O. tenuiflorum was tested in vitro and in vivo conditions against Curvularia spp. Compared to other treatments, O. tenuiflorum had high percentage of disease inhibition under both in vitro and in vivo conditions. Therefore, O. tenuiflorum is found to be the best botanical agent against Curvularia root rot on L. repens. Potential of this biocontrol agent for other plants need to be investigated and the further research on O. tenuiflorum need to be carried out to find out the compound responsible for such suppression.
Keywords: Biocontrol agent; Curvularia spp; Ludwigia repens; Ocimum tenuiflorum; root rot; Trichoderma